Are Market Makers Uninformed and Passive? Signing Trades in The Absence of Quotes - Michel van der Wel; Albert Menkveld; Asani Sarkar (Tinbergen Institute, 2009)
We develop a new likelihood-based approach to sign trades in the absence of quotes. It is equally efficient as existing MCMC methods, but more than 10 times faster. It can deal with the occurrence of multiple trades at the same time, and noisily observed trade times. We apply this method to a high-frequency dataset of the 30Y U.S. treasury futures to investigate the role of the market maker. Most theory characterizes him as an uninformed passive liquidity supplier. Our results suggest that some market makers actively demand liquidity for a substantial part of the day and are informed speculators.
Keywords: C22; G14; E44; 330; market microstructure; signing trades; market makers; treasury futures; discount rate; Informationsverhalten; Börsenmakler; Wertpapierhandel; Staatspapier; Marktmikrostruktur; Theorie